1980
DOI: 10.2105/ajph.70.9.1000
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a pilot child playground injury prevention project in New York State.

Abstract: Following a child playground equipment injury prevention project conducted in New York State in 1977, there was a 42 per cent reduction in playground equipment hazards, and a 22.4 per cent reduction in playground related injuries treated in the two largest hospitals of one of the program sites. Knowledge about unsafe playground practices and equipment hazards improved after the workshops for playground personnel. This approach to injury prevention deserves further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

1982
1982
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 6 publications
0
19
0
Order By: Relevance
“…This review found six studies that met all the inclusion criteria 16–21 . Two studies were designed with community controls for comparison with the intervention communities 16,17 .…”
Section: Resultsmentioning
confidence: 99%
“…This review found six studies that met all the inclusion criteria 16–21 . Two studies were designed with community controls for comparison with the intervention communities 16,17 .…”
Section: Resultsmentioning
confidence: 99%
“…One study in New York involving a 40minute workshop for teachers and playground supervisors resulted in a 42 per cent reduction in hazards from playground equipment and a 22.4 per cent reduction in injuries (Fisher et al 1980). One study in New York involving a 40minute workshop for teachers and playground supervisors resulted in a 42 per cent reduction in hazards from playground equipment and a 22.4 per cent reduction in injuries (Fisher et al 1980).…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Although the epidemiology of injuries to children has been well studied,7'9 little is known about parents' knowledge and attitudes concerning childhood injury. One (1) assess parental attitudes and knowledge of childhood injury on a na¬ tional level; (2) Fig 1. Half of the parents surveyed report¬ ed their belief that "most burns children receive are from fires." Parents of youn- (Table 3).…”
mentioning
confidence: 99%